The effects of resveratrol on metabolic status in patients with type 2 diabetes mellitus and coronary heart disease. Issue 9 (5th September 2019) - Hoseini, Asma; Namazi, Gholamreza; Farrokhian, Alireza; Reiner, Željko; Aghadavod, Esmat; Bahmani, Fereshteh; Asemi, Zatollah
Abstract : This study was performed to investigate the effects of resveratrol on metabolic status in patients with type 2 diabetes mellitus (T2DM) and coronary heart disease (CHD). Abstract : This study was performed to investigate the effects of resveratrol on metabolic status in patients with type 2 diabetes mellitus (T2DM) and coronary heart disease (CHD). This randomized, double-blind, placebo-controlled trial was performed with 56 patients having T2DM and CHD. The patients were randomly divided into two groups to receive either 500 mg resveratrol per day ( n = 28) or placebo ( n = 28) for 4 weeks. Resveratrol reduced fasting glucose ( β −10.04 mg dL −1 ; 95% CI, −18.23, −1.86; P = 0.01), insulin ( β −1.09 μIU mL −1 ; 95% CI, −1.93, −0.24; P = 0.01) and insulin resistance ( β −0.48; 95% CI, −0.76, −0.21; P = 0.001) and significantly increased insulin sensitivity ( β 0.006; 95% CI, 0.001, 0.01; P = 0.02) when compared with the placebo. Resveratrol also significantly increased HDL-cholesterol levels ( β 3.38 mg dL −1 ; 95% CI, 1.72, 5.05; P < 0.001) and significantly decreased the total-/HDL-cholesterol ratio ( β −0.36; 95% CI, −0.59, −0.13; P = 0.002) when compared with the placebo. Additionally, resveratrol caused a significant increase in total antioxidant capacity (TAC) ( β 58.88 mmol L −1 ; 95% CI, 17.33, 100.44; P = 0.006) and a significant reduction in malondialdehyde (MDA) levels ( β −0.21 μmol L −1 ; 95% CI, −0.41, −0.005; P = 0.04) when compared with the placebo. Resveratrol upregulated PPAR-γ ( P = 0.01) and sirtuin 1 (SIRT1) ( P = 0.01) in the peripheral blood mononuclear cells (PBMCs) of T2DM patients with CHD. Resveratrol supplementation did not have any effect on inflammatory markers. Four-week supplementation of resveratrol in patients with T2DM and CHD had beneficial effects on glycemic control, HDL-cholesterol levels, the total-/HDL-cholesterol ratio, TAC and MDA levels. Resveratrol also upregulated PPAR-γ and SIRT1 in the PBMCs of T2DM patients with CHD.